A Case of Spondyloarthritis in Patient Affected by Unicentric Castleman's Disease Effectively Managed with Surgery Resection and Tocilizumab Treatment. (23rd January 2018) - Filippini, M.; Cartella, S.; Bonzanini, O.; Morello, E.; Tincani, A.
Abstract : A 38-year-old woman was referred to our hospital for rheumatologic manifestations (migrant arthritis and tenosynovitis), without psoriasis or family history of psoriasis, gastroenteric manifestations, or recent genitourinary infections. The instrumental and laboratory tests have suggested a diagnosis of undifferentiated seronegative HLA-B27-positive spondyloarthritis with predominantly peripheral involvement. The symptoms were very severe and resistant to anti-inflammatory drugs and steroids. She had a history of hyaline-vascular unicentric Castleman's disease (HBV, HIV, and HHV-8 negative) treated with surgery resection. After a first pharmacological attempt with sulfasalazine (suspended for urticarial rash), we managed the patient with monotherapy tocilizumab 8 mg/kg, with full response of rheumatologic manifestations. The efficacy of tocilizumab was confirmed even after a follow-up of three years. Our experience seems to describe a new late-onset autoimmune disease (only 21 cases described in literature) potentially related to Castleman's disease. The patient experienced marked improvement from IL-6-based therapy (tocilizumab).